Correlations with Congenital Syphilis in the United States: A Cross-Sectional Study - Virginia C. Hughes (International Journal of Sexually Transmitted Diseases, 2023)
Syphilis is caused by the bacterium Treponema pallidum and is transmitted from human to human through sexual contact. Congenital syphilis (CS) occurs when the mother transmits the infection to the fetus. Clinical manifestations of CS include anemia, hepatosplenomegaly, blindness, deafness, meningitis, and deformities in bone structure. The number of cases of CS have increased over the past decade in the United States according to the CDC. A study was conducted correlating the number of Medicaid enrollees in 2020, the number of uninsured persons in 2020, and the number of cases of COVID-19 in 2020 to cases of CS in the United States in 2021. A Spearman rank correlation analysis was done using SPSS. Results were statistically significant for all three pairs of variables with positive correlations; Medicaid enrollment and CS cases (r = 0.735, P<.05), uninsured persons with CS cases (r = 0.713, P<.05), COVID-19 cases and CS cases (r = 0.689, P<.05). Reasons for the increase in CS cases are multifactorial, including variations in state laws regarding syphilis screening in the prenatal period, differences in provider processes for persons on Medicaid, persons uninsured, and restrictions to accessing healthcare providers during the COVID-19 pandemic. Future studies should include questionnaires and interviews with women on their experiences during prenatal visits in regards to syphilis screening, particularly women covered by Medicaid, and surveys completed by healthcare providers to gain insight and to identify factors that affect a woman not being tested for syphilis during her pregnancy.
Keywords: congenital syphilis